2015
DOI: 10.1007/s00299-015-1847-0
|View full text |Cite
|
Sign up to set email alerts
|

Sp-miR396a-5p acts as a stress-responsive genes regulator by conferring tolerance to abiotic stresses and susceptibility to Phytophthora nicotianae infection in transgenic tobacco

Abstract: Overexpression of Sp-miR396a-5p in tobacco increased tolerance to salt, drought, cold stress and susceptibility to Phytophthora nicotianae infection. MicroRNA396 (miR396) is one of the conserved microRNA families in plants, and it targeted growth-regulating factors (GRFs) family. The GRF transcription factors are associated with growth and stress responses. However, the molecular mechanisms of miR396 responding to environmental stresses are elusive. The purpose of this study was to explore the function of toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…Also, different stresses lead to changes in miR396 accumulation, including interactions with nematodes, bacteria, oomycetes and abiotic stress, among others2844575859. However, little is known about the miR396-mediated molecular reprogramming in those different scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, different stresses lead to changes in miR396 accumulation, including interactions with nematodes, bacteria, oomycetes and abiotic stress, among others2844575859. However, little is known about the miR396-mediated molecular reprogramming in those different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal perception impinges on the activity of MIR396 promoters leading to a gradual decline in mature miR396 levels and a concomitant increase of miR396 target expression during the normal course of PTI. MiR396 targets can regulate growth and stress responses2425262728, MIM396 plants grow and develop normally. This result is in agreement with the minor changes observed in the global transcriptome in non-pathogen challenged MIM396 plants.…”
mentioning
confidence: 99%
“…For instance, our previous work has shown that the miR396 family miRNAs target growth-regulating factor (GRF) genes. Tobacco plants overexpressing Sp -miR396a-5p show increased susceptibility to P. nicotianae infection38. Although plant miRNAs have been extensively studied, few miRNAs have been discovered in microbes.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 days, the leaves were collected for RNA extraction to examine the expression levels of pi-amiR1918 and target genes. After 7 days, the relative lesion size, sporangia per leaf, and detection of dead cells were determined by ImageJ, direct counting and trypan Blue staining38, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The transgenic lines under multiple stresses launched an efficient antioxidative system involving up-regulation of CSD1, CSD2, CCS1, glutathione-S-transferase, as well as the redox stress-associated gene, SAP12 (Ma et al 2015). Chen et al (2015) described tomato miR396a-5p as a positive regulator of tolerance against multiple abiotic stresses, but a negative regulator of generating resistance against Phytophthora infestans. Overexpression of miR396a-5p from tomato in tobacco increased plant tolerance towards salinity, drought, and cold stresses primarily by targeting growth-regulating factors (GRFs).…”
Section: Mirnas In Salinity and Drought Stressmentioning
confidence: 98%